Giant exchange bias in antiferromagnetic Pr2CoFe0.5Mn0.5O6: a structural and magnetic properties study. (8th September 2022) - Anand, Khyati; Pal, Arkadeb; Joshi, Amish G; Pal, Prabir; Singh, Rahul; Yen, Peter Tsung-Wen; Huang, S M; Alam, Md; Kumari, Seema; Sathe, Vasant; Chakravarty, Sujoy; Mohan, Anita; et al.
Abstract: Antiferromagnetic (AFM) materials with a colossal exchange bias (EB) effect find applications as high-density spintronic devices. We report structural (geometrical and electronic) and magnetic studies in the polycrystalline Pr2 CoFe0.5 Mn0.5 O6 double perovskite system. The observed lack of training effect suggests the existence of robust EB. In addition, the detailed magnetic studies and Raman studies unravel the Griffith-like phase along with the spin-phonon coupling in the present system. The x-ray photoemission spectroscopy (XPS) analysis supports more than one valence state of B-site elements, which is accountable for the competition between ferromagnetic (FM) and AFM interactions in addition to the anti-site disorder in the system. The neutron measurement confirms the G-type AFM spin arrangement, accredited by the DFT calculation. The magnetic studies have correlated with the electronic structure, neutron study, and theoretical first principle calculations.